56th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2015
DOI: 10.2514/6.2015-0452
|View full text |Cite
|
Sign up to set email alerts
|

Mass Optimisation of Variable Angle Tow, Variable Thickness Panels with Static Failure and Buckling Constraints

Abstract: By taking advantage of curved fiber paths, Variable Angle Tow (VAT) laminates increase the design space for tailoring the structural behavior of thin-walled aerospace structures. In recent years, advancements in Automated Fiber Placement (AFP) and Continuous Tow Shearing (CTS) have facilitated the manufacture of these laminates. The CTS technique holds the advantage of reducing many of the manufacturing defects characteristic of the AFP process such as fiber wrinkling, tow gaps and tow overlaps, while also all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Continuous tow shearing is a new manufacturing method, leading to varying fiber angles without any gaps or overlaps, but with a thickness variation that is coupled with the change in fiber angle [32,16]. By using a genetic algorithm, coupled with a pattern-search algorithm, or using the infinite strip method, large improvements in structural performance have been shown [33,34]. A more comprehensive review of optimization strategies can be found in Ghiasi et al [35] To exploit the possibilities of VSL fully, a three-step approach has been developed at Delft University of Technology.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous tow shearing is a new manufacturing method, leading to varying fiber angles without any gaps or overlaps, but with a thickness variation that is coupled with the change in fiber angle [32,16]. By using a genetic algorithm, coupled with a pattern-search algorithm, or using the infinite strip method, large improvements in structural performance have been shown [33,34]. A more comprehensive review of optimization strategies can be found in Ghiasi et al [35] To exploit the possibilities of VSL fully, a three-step approach has been developed at Delft University of Technology.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous tow shearing is a new manufacturing method, leading to varying fibre angles without any gaps or overlaps, but with a thickness variation that is coupled with the change in fibre angle [22,23]. Using a genetic algorithm, coupled with a pattern-search algorithm, or using the infinite strip method large improvements in structural performance have been shown to be possible [24,25]. A more comprehensive review of optimisation strategies can be found in Ghiasi et al [26] The lamination parameters are optimised in step one of the three-step optimisation approach, which has the disadvantage that a fibre angle retrieval step is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Higherorder finite elements have also been used to study the bending [36] and vibrational response [37,38] of VAT plates. At the same time, the pseudo-spectral Differential Quadrature Method (DQM) has been shown to be a fast, accurate and computationally efficient technique for solving the variable-coefficient higherorder differential equations for bending [39], buckling [26,40] and postbuckling [27,41] of VAT plates and cylindrical shells [42,43]. For a recent review on the differential quadrature method the interested reader is directed to [44].…”
Section: Introductionmentioning
confidence: 99%
“…For a recent review on the differential quadrature method the interested reader is directed to [44]. The work by White et al [42], Raju et al [45] and Groh & Weaver [43] has shown the efficiency and effectiveness of using Koiter's asymptotic analysis within a DQM framework to study the critical and post-critical behavior of VAT plates and shells. Furthermore, a strong-form finite element method based on DQM has been used to study the static [46] and vibrational response [47] of doubly-curved VAT laminates.…”
Section: Introductionmentioning
confidence: 99%